Phytochemical Screening and Anti-Microbial Properties of Medicinal Plants of Dhunkharka Community, Kavrepalanchowk, Nepal - Gyawali, Rajendra (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACTMedicinal plants serve as the main source of medicine to poor communities that do not have access to modern medical services. This research deals with the phytochemical and biological screening of different plants collected form Dhunkharka village of Kavrepalanchowk district, Nepal. Stephania glandulifera, Cuscuta reflexa, Bergenia ciliata, Melia azadirachta, Drymaria diandra, Jasminum humile, Astilbe rivularis, Oxalis corniculata, and Viola serpens were rich in flavanoids and glycosides. Methanolic extract was used for phytochemical screening and antimicrobial activities. Though there are several plants used by Dhunkharka community, only Jasminum humile and Oxalis corniculata extract showed slight antibacterial effect on human pathogenic bacterial strain E. coli. Methanolic extract of Astilbe rivularis exhibited highest antibacterial effect against E. coli while each bacterial strain varies in its sensitivity.